MiR-663a, regulated by lncRNA GAS5, contributes to osteosarcoma development through targeting MYL9. (December 2020) - Zhao, S; Xiong, W; Xu, K
Osteosarcoma is characterized by high malignancy and high metastasis rate, resulting in high mortality and disability. MiR-663a has been reported in a variety of tumors to promote tumorigenesis. However, miR-663a has not been reported in the pathogenesis of osteosarcoma. Bioinformatics analysis and experiments including real-time quantitative polymerase chain reaction (RT-qPCR), luciferase reporter, 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay, Western blot, RNA immunoprecipitation, and flow cytometry assay were applied to explore the function and mechanism of miR-663a in MG63, U2OS, Saos-2, SF-86, and hFOB1.19 cells. In this study, we found that miR-663a is highly expressed in osteosarcoma. At the same time, we discovered that miR-663a facilitates cell proliferation and migration, whereas suppresses cell apoptosis in osteosarcoma. Through a series of biological experiments, it was found that miR-663a regulates the cellular process in osteosarcoma by modulating the expression of MYL9. In addition, we also found that long noncoding RNA (lncRNA) GAS5 serves as a molecular sponge for miR-663a and regulates the progression of osteosarcoma via the ceRNA mechanism. We uncover that miR-663a promotes osteosarcoma development through targeting MYL9, which was regulated by lncRNA GAS5.